2012
DOI: 10.4236/fns.2012.39174
|View full text |Cite
|
Sign up to set email alerts
|

Chips Production from Jerusalem Artichoke (<i>Helianthus tuberosus</i> L.)

Abstract: Jerusalem artichoke has been cultivated in various regions without any special breeding technique. As a food, Jerusalem artichoke has a characteristic flavour and functional ingredients including inulin, other dietary fibers, minerals and traces of polyphenol. The production of chips from Jerusalem artichoke was examined in this study because it contains high amount of inulin. Inulin gives health promoting effects especially for the people suffering from diabetes. Firstly,chips production from Jerusalem artich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
3
6
0
1
Order By: Relevance
“…However, the blends containing 10, 20 and 30% red radish scored highest in overall acceptability, but it was significantly differences compared to which contain 40 and 50% artichoke . In general, the beef burger blends showed that the high consumer acceptable with respect to all sensory properties these results agreement with those obtained by Baltacıoğlu and Esin,(2012) who reported that the cooking methods were used for chips production from artichoke.…”
Section: Sensory Evaluation:-supporting
confidence: 90%
See 1 more Smart Citation
“…However, the blends containing 10, 20 and 30% red radish scored highest in overall acceptability, but it was significantly differences compared to which contain 40 and 50% artichoke . In general, the beef burger blends showed that the high consumer acceptable with respect to all sensory properties these results agreement with those obtained by Baltacıoğlu and Esin,(2012) who reported that the cooking methods were used for chips production from artichoke.…”
Section: Sensory Evaluation:-supporting
confidence: 90%
“…Data in table(3) showed that potassium represented the highest value of mineral content while manganese and cupper constituted the lowest value of both raw and cooked samples of red radish and artichoke . These results are in agreement with those obtained byLópez et.…”
mentioning
confidence: 99%
“…It can be suggested that frying (stronger processing conditions) led at the same time to greater darkness (L*) and to the generation of redness via Maillard reaction and caramelisation reactions that was previously described by Ngadi et al [29] and Kerr [30]. Similar observation was made in case of frying and microwave cooking of Jerusalem Artichoke chips [31].…”
Section: Storage Time (Week)supporting
confidence: 69%
“…Yüksel (2014) observed that wheat and corn chips showed 21.48–34.02% and 22.51–28.28% oil absorption, respectively. Baltacıoğlu & Esin (2012) reported that the fat contents of commercial fried corn chips, commercial fried potato chips and commercial baked potato chips were determined as 25.0%, 31.0% and 15.89%, respectively. Similarly, corn chips were reported to contain 24.90% fat (Sayaslan et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Yüksel (2014) observed that L* , a* and b* were 64.53, 9.39 and 30.21 for wheat chips fried for 60 s at 180 °C and 54.84, 16.41 and 41.22 for corn chips fried for 60 s at 180 °C, respectively. It was also observed that addition of spices and cooking method (baking or frying) significantly affected colour characteristics of chips containing Jerusalem artichoke (Baltacıoğlu & Esin, 2012). The Maillard reaction between amino acids and reducing sugars results in non‐enzymatic browning, which reduces the brightness of the product.…”
Section: Resultsmentioning
confidence: 99%